Logarithmic Bounds for Oscillatory Singular Integrals on Hardy Spaces - Hussain Al-Qassem; Leslie Cheng; Yibiao Pan (Journal of Function Spaces)
We establish a logarithmic bound for oscillatory singular integrals with quadratic phases on the Hardy space H1(Rn). The logarithmic rate of growth is the best possible.